William O. Douglas papers - Douglas, William O. (William Orville), 1898-1980.
Correspondence, speeches, writings, subject files, Supreme Court files, financial papers, family papers and genealogy, printed matter, photographs, and other papers documenting Douglas's legal career, his concern for the environment, and other interests. Supreme Court files (1938-1975) comprise the bulk of the collection, containing correspondence, memoranda, drafts and final opinions, docket books, and printed matter relating to cases heard, as well as administrative files of Douglas and his staff. Other papers pertain to his career prior to his Supreme Court appointment, particularly as a faculty member at the law schools of Yale and Columbia universities (1925-1936), director of the Protective Committee Study (1936) of the Securities and Exchange Commission, member and chairman of the SEC (1936-1939), and advisor to President Franklin D. Roosevelt. Environmental files include material on conservation, C & O Canal, wildlife, preservation of wilderness areas, and pollution of air and water.
Other topics include Douglas's 1928-1929 study of business failures and bankruptcy laws in the United States, corporate finance, his advocacy for a combined business and law school curriculum at Harvard and other universities, legal affairs of the Chicago, Milwaukee, St. Paul, and Pacific Railroad Company, travels in the U.S. and abroad, his interest in botany and collecting specimens from the Middle East and elsewhere, Fund for the Republic, mass education movement, Albert Parvin Foundation, attempt to impeach Douglas from the Supreme Court, U.S. policy toward Asia and recognition of Red China, support of Israel, U.S. Constitution, Bill of Rights, and the First Amendment, and family matters.
Correspondents include P.K. Bannerjee, George Eugene Bates, David T. Bazelon, Martha Douglas Bost, Jim D. Bowmer, Charles Edward Clark, Clark M. Clifford, Sidney M. Davis, Irving Dilliard, Arthur Douglas, Mercedes D. Douglas Eichholz, Abe Fortas, Jerome Frank, Elon James Gilbert, Dagmar S. Hamilton, John J. Hooker, Edwin Palmer Hoyt, Robert Maynard Hutchins, Eliot Janeway, Lyndon B. Johnson, Robert F. Kennedy, Robert Lantz, Francis Thomas Maloney, A. Howard Meneely, Richard L. Neuberger, Ram Rahul, Fred Rodell, Franklin D. Roosevelt, Carrol M. Shanks, J. Howard Shubert, Marshall L. Small, Richard J. Smith, Helen M. Strauss, Phil Tippin, and Y.C. James Yen.
Library of Congress Geography and Map Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Associate justice of the U.S. Supreme Court, chairman of the U.S. Securities and Exchange Commission, and professor of law.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bannerjee, P. K. -- Correspondence; Bates, George Eugene -- Correspondence; Bazelon, David T., -- 1923- -- Correspondence; Bost, Martha Douglas, -- 1897- -- Correspondence; Bowmer, Jim D. -- Correspondence; Clark, Charles Edward, -- 1889-1963 -- Correspondence; Clifford, Clark M., -- 1906-1998 -- Correspondence; Davis, Sidney M. -- Correspondence; Dilliard, Irving, -- 1904-2002 -- Correspondence; Douglas, Arthur, -- 1902- -- Correspondence; Eichholz, Mercedes D. Douglas -- Correspondence; Fortas, Abe -- Correspondence; Frank, Jerome, -- 1889-1957 -- Correspondence; Gilbert, Elon James, -- 1897-1978 -- Correspondence; Hamilton, Dagmar S. -- Correspondence; Hooker, John J. -- Correspondence; Hutchins, Robert Maynard, -- 1899-1977 -- Correspondence; Hoyt, Edwin Palmer -- Correspondence; Janeway, Eliot -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kennedy, Robert F., -- 1925-1968 -- Correspondence; Lantz, Robert -- Correspondence; Maloney, Francis Thomas, -- 1894-1945 -- Correspondence; Meneely, A. Howard -- 1899-1961 -- Correspondence; Neuberger, Richard L. -- 1912-1960 -- Correspondence; Rahul, Ram -- Correspondence; Rodell, Fred, -- 1907-1980 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Shanks, Carrol M. -- 1898- -- Correspondence; Shubert, J. Howard, -- -1951 -- Correspondence; Small, Marshall L. -- Correspondence; Smith, Richard J. -- 1903- -- Correspondence; Strauss, Helen M. -- -1987 -- Correspondence; Tippin, Phil -- Correspondence; Yen, Y. C. James, -- 1893-1990 -- Correspondence; Douglas family; United States; United States. -- Supreme Court; Albert Parvin Foundation; Chicago, Milwaukee, St. Paul, and Pacific Railroad Company; Columbia University. -- School of Law -- Faculty; Fund for the Republic; Harvard Law School -- Curricula; Harvard University. -- Graduate School of Business Administration -- Curricula; Yale Law School -- Faculty; Air -- Pollution; Bankruptcy -- United States; Botany; Business education -- Curricula; Business failures -- United States; Conservation of natural resources; Constitutional amendments -- United States; Constitutional law -- United States; Corporations -- United States -- Finance; Economic assistance, American -- Israel; Environmental protection; Fundamental education; Impeachments -- United States; Law -- Study and teaching; Law -- Study and teaching -- Curricula